Irritable Bowel Syndrome with Diarrhea (IBS-D): Effects of Clostridium butyricum CBM588 Probiotic on Gastrointestinal Symptoms, Quality of Life, and Gut Microbiota in a Prospective Real-Life Interventional Study - Francesco Di Pierro; Fabrizio Ficuccilli; Laura Tessieri; Francesca Menasci; Chiara Pasquale; Amjad Khan; Fazle Rabbani; Nazia Mumtaz Memon; Massimiliano Cazzaniga; Alexander Bertuccioli; Mariarosaria Matera; Ilaria Cavecchia; et al. (Microorganisms)
Diarrhea-predominant irritable bowel syndrome (IBS-D) is a functional gastrointestinal disorder characterized by altered motility, abdominal pain, and dysbiosis—particularly reduced biodiversity and a lower abundance of butyrate-producing bacteria. Strategies that modulate the gut microbiota may offer therapeutic benefit. Clostridium butyricum (C. butyricum) CBM588 is a butyrate-producing probiotic with immunomodulatory properties and potential efficacy in treating gastrointestinal disorders. This pragmatic, prospective, open-label, single-arm interventional study assessed the clinical, microbial, and safety-related effects of an 8-week CBM588 supplementation, along with a low-fiber and low-residue diet, in 205 patients with IBS-D who attended Quisisana Nursing Home Hospital, Rome, Italy, between November 2024 and February 2025. The primary outcomes included the global symptom response, the Bristol Stool Scale (BSS), stool frequency, diarrhea episodes, abdominal pain (severity and frequency), bloating, bowel dissatisfaction, quality of life (QoL), safety, and treatment tolerability—measured using the IBS Symptom Severity Scale (IBS-SSS) and a standardized tolerability scale. CBM588, in patients treated with a low-fiber and low-residue diet, significantly improved all clinical endpoints, with a >80% reduction in diarrhea episodes; ~60% reductions in stool frequency and abdominal pain; and >50% improvements in bloating, bowel dissatisfaction, and QoL. Treatment was well tolerated (mean tolerability score 8.95 ± 0.88), with >95% adherence, and no serious adverse events were reported. The secondary outcomes included changes in gut microbiota. In a subset of patients, 16S rRNA gene sequencing showed increased α-diversity and enrichment of butyrate-producing genera (Agathobacter, Butyricicoccus, Coprococcus), which correlated with symptom improvement. Bloating increased in some patients, possibly related to fermentation activity. These findings support the C. butyricum CBM588 probiotic strain as a safe, well-tolerated, and microbiota-targeted intervention for IBS-D. Randomized controlled trials are warranted to confirm efficacy.